Evaluation of Speech and Language Features of Children Born after Assisted Reproductive Techniques - Soudabeh Nouri; Ramin Mozaffari-Kermani; Jalil Kouhpayeh-Zadeh; Shabnam Zoljalali (University of Social Welfare and Rehabilitation Sciences, 2010)
Objective: To evaluate some speech and language features of children born after assisted reproductive techniques (ART). Materials & Methods: In this descriptive and analytical study, fifty children between 0- 49 months were selected simply and conveniently by consecutive method and evaluated via interview with their parents and clinical observation, by a speech and language pathologist. A questionnaire was completed after parent interview. The ELM-2 (Early Language Milestone Scale-2), MLU (Mean Length Utterance) test and POSP (Paediatric Oral Skill Pakage) were employed. Data were analyzed by Independent T Test, Mann-Whitney Test, Chi Square and Kolmogorov Smirnov Test. Results: 33 children (66%) were born through intracytoplasmic sperm injection (ICSI) , and the reminder through invitro fertilization (IVF) or intrauterine insemination (IUI). Mean Length Utterance (MLU) was 3.3 words. 8% of these children had some structural anomalies in speech organs and 6% of them showed speech organs dysfunction. There was no gender priority in MLU (P=0.069), cooing (P=0.125), number of words (P=0.079) and structure and function of speech organs (P=0.327). There was significant difference between boys and girls in lalling (P=0.026). Conclusion: Speech and language of children born after assisted reproductive techniques (ART) are normal but more comprehensive studies are needed.